Saúde mental no cotidiano da formação em enfermagem: modo-de-ser-docente - QUEIROZ, Aline Macêdo de (Universidade Federal do Pará, 2022)
Phenomenological qualitative research approach, which used as a theoretical and methodological framework philosophy of Martin Heidegger expressed in his work Being and Time. Study conducted at the School of Nursing, Federal University of Pará in the second half of 2013 and aimed to: reveal the meanings and feelings that the nursing professors of the second and third semesters of the undergraduate nursing of Federal University of Pará express on mental health in daily life to be teaching. Participated in this study of nine nursing professors curricular activities Introduction to Nursing ( 3 ) Integral Attention to Women, Children and Adolescents ( 2 ), Health Care for the older persons ( 2 ), Educational Process I ( 1 ). Professional Practice and Health ( 1 ). The expressed by teachers was captured by phenomenological interview scheduled with each teacher and analyzed by ontic instance as regards the vague understanding and median. Five units of meanings emerged: US1 mental health is natural phenomenon that manifests itself in the freedom to be and how to be with each other in a balanced relationship. US2 the significance of mental health as the essence of the experiences expressed in the possibility of access to the things of the world. US3 mental health is revealed in everyday nursing practice in different stages of life in a given occupation simply. US4 Mental Health manifested in the training process as a secondary event. US5 how to be a teacher in their life experience influences relations with each other in the training process. The revealed in the study, through what was spoken, perceived and experienced, expressed concern that mental health is an event, however this does not constitute as possibilities, ie, there is an early occupation of mental health as content formal study of this or that activity. It is possible that teachers in their way of being able to open up again, launch into the world and promote changes in the daily training of nurses, taking care of mental health, because even without this in the syllabus content there the recognition of its existence and its importance in the temporality of life of the people.